A Retrospective Review of the Outcomes and Utility of Percutaneous Radiofrequency Rhizotomy for Trigeminal Neuralgia Using Anatomic Landmark Guidance in Asleep Patients. Issue 5 (23rd August 2019) - Stone, Lauren E; Falowski, Steven M
Abstract: BACKGROUND: Radiofrequency rhizotomy is a percutaneous procedure for trigeminal neuralgia frequently performed with intermittent awakening, although the utility and accuracy of this procedure in continuously sedated patients have not yet been evaluated. OBJECTIVE: To evaluate pain relief in patients with trigeminal neuralgia undergoing radiofrequency rhizotomy under continuous sedation. METHODS: Patients from 2012 to 2017 who underwent radiofrequency rhizotomy for trigeminal neuralgia were evaluated retrospectively. Barrow Neurological Institute Pain Intensity scores were assigned to determine relapse at 1 mo, 1 yr, 3 yr, and 5 yr. Descriptive relapse rates for patients with multiple sclerosis and those undergoing repeat procedures are also reported. RESULTS: A total of 90.8% of procedures reported Barrow Neurological Institute I-III score at 1 mo ( P  < .0001), 66.3% at 1 yr ( P  = .0012), and 71.1% at 3 yr ( P  = .0003). Duration to relapse was 3.0 and 6.0 at 1 and 3 yr, respectively. Procedures in patients with multiple sclerosis reported 100% relief at 1 mo and 87.5% relief at 1 yr ( P  = .0099). The presence of numbness and postoperative medication changes were not associated with pain relief ( P  = .0063, P  = .1338). CONCLUSION: The use of continuous sedation in radiofrequency rhizotomy for trigeminal neuralgia provides pain relief comparable to the recorded literature rate for procedures with intermittent awakening. Graphical Abstract: